Exploring tactical choices and game design outcomes in a simple wargame 'Take that Hill' by a systematic approach using experimental design. - Mark Flanagan; Adrian Northey; Ian Robinson (Serious Games Society, 2021)
Experimental Design (ED) technique is a proven analytical method used in the chemicals industry. We have taken this approach and applied it to Phil Sabin's 'Take That Hill', a simple wargame presented at Connections 2014. By evolving the tactical turn game choices into playable full-game strategies, a descriptive set of game outcomes can be delivered and optimised to produce winning strategies. This provides a systematic approach to testing a game, with full post-game deconstructive analysis which is capable of being used to identify flaws, and find optimal strategies in playing the game.  The most successful strategies found by ED outperformed individual strategies developed by experienced players. ED allowed pairing of obvious good play with seemingly counterintuitive play that were found to work well in unexpected combinations.